2015
DOI: 10.1097/ccm.0000000000000880
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Outcomes and Postresuscitation Care of Patients With Myoclonus Following Cardiac Arrest*

Abstract: Nine percent of cardiac arrest survivors with myoclonus after cardiac arrest had good functional outcomes, usually in patients without associated epileptiform activity and after prolonged hospitalization. Deaths occurred early and primarily after withdrawal of life support. It is uncertain whether prolonged care would yield a higher percentage of good outcomes, but myoclonus of itself should not be considered a sign of futility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
93
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 44 publications
(21 reference statements)
8
93
0
7
Order By: Relevance
“…Coming to clinical prognosticators, lack of corneal reflexes had the lowest false positive prediction of poor outcome (0 %); the false positive rate regarding occurrence of myoclonus was 14 %, especially if a normal voltage was observed, broadly confirming other recent observations [12,13]; false positivity for the lack motor response was identical, also in line with previous reports [12]. Finally, the authors propose a two-step approach for outcome prognosis, starting with EEG at 24 h and completing it with corneal reflexes at 72 h. This is a single-center analysis performed in an environment with the highest expertise for cEEG interpretation, potentially limiting its generalizability; the poor outcome rate of 71 % is higher than that in other recent series [5,12], but outcome assessment at discharge might have underestimated the recovery of some patients, especially for those in the inhomogeneous category of GOS (or CPC) = 3.…”
supporting
confidence: 75%
“…Coming to clinical prognosticators, lack of corneal reflexes had the lowest false positive prediction of poor outcome (0 %); the false positive rate regarding occurrence of myoclonus was 14 %, especially if a normal voltage was observed, broadly confirming other recent observations [12,13]; false positivity for the lack motor response was identical, also in line with previous reports [12]. Finally, the authors propose a two-step approach for outcome prognosis, starting with EEG at 24 h and completing it with corneal reflexes at 72 h. This is a single-center analysis performed in an environment with the highest expertise for cEEG interpretation, potentially limiting its generalizability; the poor outcome rate of 71 % is higher than that in other recent series [5,12], but outcome assessment at discharge might have underestimated the recovery of some patients, especially for those in the inhomogeneous category of GOS (or CPC) = 3.…”
supporting
confidence: 75%
“…The incidence of posthypoxic myoclonus (PHM) in resuscitated patients with postanoxic encephalopathy (PAE) is 19%, and only 9–14% of these patients recover with mild to no cognitive deficits 4, 5, 6…”
Section: Introductionmentioning
confidence: 99%
“…The survival of comatose patients with generalized PHM admitted at an intensive care unit (ICU) is reported to be poor (±3%) in comparison with focal PHM patients (±17%) 4, 5. Generalized PHM is associated with a subcortical origin.…”
Section: Introductionmentioning
confidence: 99%
“…There are several malignant EEG patterns seen in patients after CRA, including burst suppression, nonreactive background, alpha coma, generalized status epilepticus, and lateralized (LPDs) or generalized periodic discharges (GPDs; 4,5,17,24,29,37). Multiple studies have demonstrated that these EEG patterns, as well as others that signify severe brain injury, predict worse outcomes when found in those with PHM after CRA (4,5,21,(24)(25)(26)29).…”
Section: Neurophysiological Studies May Help Differentiate "Benign" Amentioning
confidence: 99%
“…Multiple studies have demonstrated that these EEG patterns, as well as others that signify severe brain injury, predict worse outcomes when found in those with PHM after CRA (4,5,21,(24)(25)(26)29). This was also described in a review by Gupta et al that included 37 articles, of which a number are included in this review (4,11,12,24,27,29, and a number of cases of LAS also described in Freund et al [3]).…”
Section: Neurophysiological Studies May Help Differentiate "Benign" Amentioning
confidence: 99%